2022
DOI: 10.3389/fonc.2022.840038
|View full text |Cite
|
Sign up to set email alerts
|

WASF2 Serves as a Potential Biomarker and Therapeutic Target in Ovarian Cancer: A Pan-Cancer Analysis

Abstract: BackgroundWiskott-Aldrich syndrome protein family member 2 (WASF2) has been shown to play an important role in many types of cancer. Therefore, it is worthwhile to further study expression profile of WASF2 in human cancer, which provides new molecular clues about the pathogenesis of ovarian cancer.MethodsWe used a series of bioinformatics methods to comprehensively analyze the relationship between WASF2 and prognosis, tumor microenvironment (TME), immune infiltration, tumor mutational burden (TMB), microsatell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…The genes WASF2 and LRIG2 have been linked with many forms of cancer detection as well ( Wang et al 2014 ; Kitagawa et al 2019 ). WASF2 expression levels have been studied as a biomarker in detection of pancreatic ( Kitagawa et al 2019 ) and ovarian cancers ( Yang et al 2022 ), whereas LRIG2 has been identified as a biomarker for detection of nonsmall cell cancer ( Wang et al 2014 ). On the other hand, SDAD1 has been identified as a gene responsible for suppressing colon cancer metastasis ( Zeng et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The genes WASF2 and LRIG2 have been linked with many forms of cancer detection as well ( Wang et al 2014 ; Kitagawa et al 2019 ). WASF2 expression levels have been studied as a biomarker in detection of pancreatic ( Kitagawa et al 2019 ) and ovarian cancers ( Yang et al 2022 ), whereas LRIG2 has been identified as a biomarker for detection of nonsmall cell cancer ( Wang et al 2014 ). On the other hand, SDAD1 has been identified as a gene responsible for suppressing colon cancer metastasis ( Zeng et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…These top significant 6 genes, including ATP1A1, KMT2E, RAD23A, TRR, WASF2 and DNAJC9, were screened from the 34 negatively-related stemness genes, using the random survival forest algorithm. ATP1A1, KMT2E and WASF2 were known as the hallmarker of cancers and overexpression of these genes promote the survival of cancer cells ( 20 22 ), while RAD23A acts as a negative regulator of anti-virus response and might correlate directly with the HPV infection ( 23 ). TPR is a nucleoporin which prevents DNA damage ( 24 ) and DNAJC9 is a dual histone chaperone and heat shock cochaperone, which recruits HSP70 enzymes to guard histone structural integrity ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…ABI3BP is a potential partner of ABI3, and previous studies have shown that their expression levels are synchronized during cancer progression ( Latini et al, 2011 ). Moreover, there is existing literature demonstrating the important roles of ABI3BP, WASF2, RUNX1T1, and TNFAIP8L2 in cancer processes through pan-cancer analysis ( Bai et al, 2022 ; Lin, 2022 ; Yang et al, 2022 ; Feng et al, 2023 ). This analysis suggests that ABI3 may influence cancer progression by interacting with the aforementioned genes.…”
Section: Resultsmentioning
confidence: 99%